Survival rate and use of revision components in total knee arthroplasty following unicompartmental knee arthroplasty or proximal tibial osteotomy: an analysis of 11,983 procedures from the Dutch Arthroplasty Register - Maarten R Huizinga; Astrid J de Vries; Liza N van Steenbergen; Reinoud W Brouwer (Acta Orthopaedica)
Background and purpose: Unicompartmental osteoarthritis of the knee can be treated with high tibial osteotomy (HTO) or unicompartmental knee arthroplasty (UKA). This study aimed to investigate the use of revision components in total knee arthroplasty (TKA) after HTO or UKA and to investigate the revision-free survival of the 2 groups of TKA at different time points, including reasons for revision. Methods: TKAs after HTO and revision TKAs after failed UKA in the years 2007–2022 were selected from the Dutch Arthroplasty Register. For complexity, the usage of revision components was analyzed. Kaplan–Meier survival analysis was used to estimate survival rate. Multivariable Cox proportional hazards regression analyses were used to estimate the risk of revision, considering potential confounders. Indications of revision were evaluated. Results: 11,983 procedures were analyzed (9,835 HTO-TKA and 2,148 UKA-TKA). In the HTO-TKA group, 3% had revision components in the TKA compared with 22% in the UKA-TKA group (P < 0.001). After 12 years’ follow-up the revision-free survival was 90.4% (95% confidence interval [CI] 89.6–91.2) for HTO-TKA and 81.7% (CI 79.3–84.1) for UKA-TKA. The multivariable Cox regression analysis showed that UKA-TKA was a significant risk factor for a revision of the TKA (hazard ratio 2.3, CI 1.8–2.6), compared with HTO-TKA. In both groups the most frequent reason for revision was instability, followed by patellar pain and loosening of the tibial component. Conclusion: TKAs after UKAs had higher use of revision components and a lower survival rate compared with TKAs following an HTO. The choice of surgical treatment should be considered for the young and active patient with unicompartmental knee osteoarthritis.